2019
DOI: 10.1038/s41598-019-39273-4
|View full text |Cite
|
Sign up to set email alerts
|

A RNA sequencing-based six-gene signature for survival prediction in patients with glioblastoma

Abstract: Glioblastoma (GBM) is an aggressive tumor of the central nervous system that has poor prognosis despite extensive therapy. Therefore, it is essential to identify a gene expression-based signature for predicting GBM prognosis. The RNA sequencing data of GBM patients from the Chinese Glioma Genome Atlas (CGGA) and The Cancer Genome Atlas (TCGA) databases were employed in our study. The univariate and multivariate regression models were utilized to assess the relative contribution of each gene to survival predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 51 publications
0
51
0
1
Order By: Relevance
“…There has been significant progress in understanding genomic drivers implicated in glioma tumorigenesis. Multidimensional data from genomics studies such as The Cancer Genome Atlas (TCGA) 46 , REMBRANDT study 47 , and the Chinese Glioma Genome Atlas (CGGA) 48 have identified molecular signatures associated with glioma subtypes and their prognoses 49 . Isocitrate dehydrogenase (IDH) mutation and 1p/19q co-deletion are most prominent markers associated with a more favourable prognosis 49 .…”
Section: Discussionmentioning
confidence: 99%
“…There has been significant progress in understanding genomic drivers implicated in glioma tumorigenesis. Multidimensional data from genomics studies such as The Cancer Genome Atlas (TCGA) 46 , REMBRANDT study 47 , and the Chinese Glioma Genome Atlas (CGGA) 48 have identified molecular signatures associated with glioma subtypes and their prognoses 49 . Isocitrate dehydrogenase (IDH) mutation and 1p/19q co-deletion are most prominent markers associated with a more favourable prognosis 49 .…”
Section: Discussionmentioning
confidence: 99%
“…And the combination of multiple prognostic genes seems to be more valuable and promising. Prognostic prediction models based on multiple genes combination have been established and validated in many cancers [7,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…And the combination of multiple prognostic genes seems to be more valuable and promising. Prognostic prediction models based on multiple genes combination have been established and validated in many cancers [7,18,19].…”
Section: Discussionmentioning
confidence: 99%